Kapalabhati: A physiological healer in human physiological system - Mansi Vaid; Sanjay Verma (Wolters Kluwer Medknow Publications, 2021)
The purpose of this article is to aware people about the yogic technique of Kapalabhati and its benefits. It clearly explains how Kapalabhati helps in prevention and cure of various health issues in different physiological systems in the human body. This review focuses on the role of kapalabhati in maintaining the normal functioning of organs and its contribution to curing different ailments in the human body. All the information that is given in this article is consulted from different websites, journal articles, and books and is written in a way suitable for reading even to the common public. The review discloses that Kapalabhati is that high-frequency breathing exercise, which promotes overall well-being and cures diseases. This study mainly focuses on cure of number of illnesses caused due to unhealthy living habits, impurities and different types of pollutants present in the environment, and inhalation of harmful nanoparticles and other factors responsible for creating severe to major problems in the human body. Kapalabhati works in a curative and revolutionary way to cope with the health issues and improves the overall function of the body.